Analytical diminution versus synthetic diminution in German and Spanish - Ramírez Sáinz, Laura (Revista de Filología Alemana, 2011)
This paper presents the characteristics of analytical diminution and synthetic diminution in Spanish and German. The concomitance between both languages and the results of the corpus studied are of particular interest. From this starting point the paper presents the consequences and difficulties in using analytic diminution as an alternative to synthetic diminution, owing to its importance and frequent use as a strategy in comparative studies.